Bioethical aspects in type I neurofibromatosis - Codruta Diana Petchesi; Gabriela Ciavoi; Claudia Jurca; Romana Vulturar; Marius Bembea (Amaltea Medical Publishing House, 2021)
Type I neurofibromatosis is one of the most common monogenic disorders, being caused by abnormalities of the neurofibromin gene on chromosome 17. About half of the cases are inherited, respecting the autosomal dominant inheritance criteria, the rest are de novo cases. The clinical manifestations are multisystemic and are progressively installed, presenting inter- and intra-familial variability of clinical expression. The hereditary nature, impaired quality of life and lethal potential identify numerous and various ethical dilemmas in the diagnosis, monitoring and treatment of neurofibromatosis type 1. Variable expressiveness and multisystemic clinical manifestations determine the unpredictable evolutionary character, associating bio-ethical dilemmas necessary to be managed in the clinical context of the disease. As a clinical applicability, we conclude that some of these problems could be avoided by informing and educating affected families about the disease, by increasing confidence in specialized services and by using molecular techniques in order to know as accurately as possible the genotype-phenotype correlation.